Role Performance of the Frontline Extension Agents in the Integrated Agricultural Extension Strategy of Sri Lanka - Illangasinghe, Mahanama (1998)
A novel extension strategy is in existence in Sri Lanka since 1994 integrating the extension efforts of Departments of Agriculture (DOA), Export Agriculture (DEA), Animal Production and Health (AP&H) and the Coconut Cultivation Board (CCB). Team efforts by theses agencies from national to grass root level, is a prominent feature of the Integrated Extension Strategy (IAES). Field Extension Teams (FET) were established for geographically demarcated areas (Govi Kendraya) consisting of frontline extension agents from four implementing agencies to service the farmer. The major objective of this study was thus to explore the predicting factors that influenced the role performance of these extension agents. Extension Agents from 4 of 15 districts, where lAES was active were selected randomly for the study. Two self-administered questionnaires, one to be completed by extension agents and the other by immediate supervisory officers appraising their performance formed the main source of data collection. The sample contained 275 extension agents of a total of 1364 and 201 questionnaires were collected for data analyses. The main statistical procedures employed were Exploratory Data Analysis, ANOVA, Pearson Product Correlation and Step-wise Multiple Regression. Analyses revealed that the age and experience of the respondents, of whom two thirds were males, were 43 and 17 years respectively. The extension agents had negative attitudes towards IAES. Although the quality of work was good the quantity of work performed by them was poor. They showed higher levels of motivation, role clarity and commitment and conversely low role ambiguity and role overload. Of the variables tested, some variables namely: attitudes towards GET members, role overload, valacy, participation, technical supervision and also quality, quantity and overall performances showed significant differences among the extension agents of the participating agencies in the IAES. Many variables namely: attitudes towards IAES, Guide and Extension Team (GET), motivation, valency, role commitment, role ambiguity, group cohesion, group interaction, followership, participation, technical supervision and administrative supervision showed significant relationships with the dependent variable role performance but the magnitudes of relationships shown by all variables were small. Attitudes towards GET, Role commitment, motivation, participation and technical supervision were the principal variables that could predict and explain the role performance of the extension agents. Nevertheless; attitudes towards IAES, valency, followership, group cohesiveness and administrative supervision were the other variables which could explain and predict role performance as second category predictors from the step-wise regression analyses. A distinct feature of these findings was that all the above variables collectively could predict and explain slightly over one-third of the variance in role performance. This indicated the substantial presence of various other facilitating and inhibiting factors out side the control of role incumbents.